State Laws for Autonomous Vehicle Safety, Equity, and Insurance. Issue 3 (2022) - Ehsani, Johnathon P.; Hellinger, Andrew; Stephens, Daniel K.; Shin, Mi Ran; Michael, Jeffrey; McCourt, Alexander; Vernick, Jon
Abstract: This article reviews existing state laws related to autonomous vehicle (AV) safety, equity, and automobile insurance. Thirty states were identified with relevant legislation. Of these, most states had one or two relevant laws in place. Many of these laws were related to safety and insurance requirements. Data are needed to evaluate the effectiveness of these laws in order to guide further policy development.